DIGITAL MARKETING SEBAGAI SOLUSI KEBERLANJUTAN UMKM PADA PERSPEKTIF NEGARA BERKEMBANG: SYSTEMATIC LITERATURE REVIEW - Dafina, Risty Rahma (Bussman Journal : Indonesian Journal of Business and Management, 2025)
Digitalization and business sustainability have become two critical issues in the development of Micro, Small, and Medium Enterprises (MSMEs). Digital transformation presents both opportunities and challenges for MSMEs to grow and remain resilient through the adoption of technology. This study aims to analyze the role of digital marketing in supporting the sustainability of MSMEs. The method employed is a Systematic Literature Review using the PRISMA approach on 17 selected articles sourced from the Scopus database, covering the period from 2018 to 2025. The findings indicate that digital marketing significantly impacts competitiveness, innovation, and the sustainability of MSMEs. Supporting factors such as technology, human resource capabilities, and policy support play a crucial role in the successful implementation of digital marketing in MSMEs